PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP RETURN ON EQUITY (ROE) - Ali Idrus (Misykat al-Anwar Jurnal Kajian Islam dan Masyarakat, 2018)
AbstractThis study examines the influence of internal and external factors to Return On Equity (ROE), study on sharia banks 2010-2014 period. The effectiveness of the management of Islamic banks in the operations will affect profit and equity of the bank. Return On Equity (ROE) describe profitability of an entity. In the theory of profitability there are 2 factors that affect the profitability of the bank, namely internal factors and external factors. Internal factors in this research is the Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Finance to Deposit Ratio (FDR), Operating Expenses Operating Income (BOPO) and external factors in this study are the exchange rates and inflation. While profitability in this study using a proxy Return On Equity (ROE). This study uses secondary data with samples of most Islamic banks are seven Islamic banks in Indonesia period 2010 to 2014. The results showed that the CAR, BOPO, FDR, EXCHANGE negative and significant effect on ROE. NPF negative but insignificant effect on ROE on Islamic Banks in Indonesia. While the inflation variable and not significant positive effect on ROE on Islamic Banks in Indonesia.Keywords: Return on Equity (ROE), Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Finance to Deposit Ratio (FDR), Operating Expenses Operating Income (BOPO), Exchange Rates, Inflation, Sharia Banks